Pasty hydrogen storage material and preparation method thereof
By combining metal hydride with liquid organic hydrogen carrier and using high shear stirring and interface modification technology to form a stable slurry hydrogen storage material, the problems of low hydrogen storage amount and unstable performance in the prior art are solved. Efficient and stable hydrogen storage and release are achieved.
Patent Information
- Application Number
- CN202411662535.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing liquid organic hydrogen carrier hydrogen storage materials have low hydrogen storage capacity and degraded performance under undesirable operating conditions, making it difficult to achieve efficient and stable hydrogen storage and release.
Use metal hydrides (such as magnesium hydrides, sodium aluminum hydrides, calcium hydrides) to compound them with liquid organic hydrogen carriers (such as methylcycloolefins, tetrahydronaphthalenes), and use of high shear stirring and interface modifiers , form a stable slurry hydrogen storage material. The material is subjected to multiple hydrogenation-dehydrogenation cycle tests under slow cooling and strict storage conditions to ensure stability and high efficiency.
The overall hydrogen storage capacity is improved, the stability of the material and hydrogen storage efficiency are enhanced, and the maintenance of hydrogen storage capacity and the stability of the reaction rate in multiple cycle tests is ensured.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen storage materials, and in particular to a slurry hydrogen storage material and a preparation method thereof. Background Art
[0002] Hydrogen energy is a clean and sustainable energy source, primarily using hydrogen as an energy carrier for energy storage, conversion, and utilization. It is considered an important alternative to traditional fossil fuels in the future, particularly in reducing greenhouse gas emissions and addressing climate change. Hydrogen storage is a major challenge in the development of the hydrogen energy industry. Hydrogen's low density and extremely small molecular structure present unique difficulties in storage and transportation. Currently, hydrogen is typically stored as a high-pressure gas or liquid, or as a hydride, but these technologies face challenges in safety, efficiency, and cost.
[0003] Slurry hydrogen storage materials are a new direction in hydrogen storage technology. The basic idea is to use certain chemical substances with good hydrogen storage properties to "store" hydrogen in liquid or solid form in liquid or slurry media. This type of material is generally a slurry formed by combining a hydrogen adsorbent (such as metal hydrides, hydride compounds, certain metal alloys, etc.) with a liquid medium (such as water, solvents, etc.).
[0004] The hydrogen storage capacity of liquid organic hydrogen carriers is generally low, especially at lower temperatures. If the selected liquid organic hydrogen carrier itself has limited hydrogen storage capacity, the overall hydrogen storage capacity of the composite material will also be limited. Even if the composite can lower the operating temperature and increase the hydrogen absorption and desorption rate, the overall hydrogen storage capacity may not reach the target of more than 5wt%. Due to factors such as the relative proportion of liquid and solid hydrogen carriers and interface contact, the hydrogen storage efficiency in actual operation may be lower than the theoretical prediction. Under undesirable operating conditions (such as unstable temperature and pressure or uneven heat transfer), the performance of the hydrogen storage material may be greatly reduced. Although the liquid hydrogen carrier helps to alleviate volume changes, excessive volume changes may cause the dispersion of the slurry material to change, affecting the uniformity and hydrogen storage capacity of the material. Therefore, the present invention proposes a slurry hydrogen storage material and a preparation method thereof to solve the problems mentioned in the above background technology. Summary of the Invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a slurry hydrogen storage material and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a slurry hydrogen storage material, wherein the slurry hydrogen storage material is prepared by mixing a metal hydride, a liquid organic hydrogen carrier, and an additive, and specifically comprises the following steps:
[0008] S1. Prepare raw materials and select one of magnesium hydride (MgH2), sodium aluminum hydride (NaAlH4), and calcium hydride (CaH2) as the metal hydride. The metal hydride is prepared by placing commercial magnesium powder or magnesium alloy in a high-pressure hydrogen environment at a temperature between 180-220°C for hydrogenation reaction to obtain magnesium hydride (MgH2). This process is obtained by atmosphere hydrogenation method or by directly reacting hydrogen with metallic magnesium;
[0009] Select one of methylcycloolefin (MCH) and tetralin as liquid organic hydrogen carrier;
[0010] Polyvinyl alcohol (PVA) or polyurethane (PU) is selected as an additive to improve the interfacial adhesion between the metal hydride and the liquid hydrogen carrier;
[0011] The molar ratio of the metal hydride to the liquid organic hydrogen carrier is 3.36:1. The additive does not participate in the storage of hydrogen and is not included in the molar ratio of hydrogen.
[0012] S2. Pre-treating the raw materials: preparing the metal hydride into powder to ensure that its particle size is 1-5 μm. Drying the obtained metal hydride powder in a vacuum environment to remove excess moisture and hydrogen, keeping it dry to avoid reaction with moisture in the air;
[0013] The liquid organic hydrogen carrier is purified by filtration or distillation to ensure its chemical purity. An adsorbent (such as activated carbon or molecular sieve) is used to remove moisture and other harmful substances in the organic hydrogen carrier. The liquid organic hydrogen carrier is placed in a vacuum distillation device by reducing the pressure to evaporate the substance at a lower temperature. The purity of the liquid organic hydrogen carrier is required to reach ≥99%;
[0014] Mix the liquid organic hydrogen carrier with activated carbon, stir for 10-20 minutes, and filter the mixture. The activated carbon will adsorb impurities on its surface. The filtered liquid will be a pure organic hydrogen carrier. The liquid organic hydrogen carrier requires that the particulate impurities do not exceed 0.01wt% (10ppm) and the volatile organic impurities (such as low-boiling point organic compounds) are <1000ppm (ideally <500ppm).
[0015] S3. Mixing of materials: In a closed stirring container, add the metal hydride powder to the liquid organic hydrogen carrier and use a high shear mixer to mix them evenly. The stirring speed is set at 500-2000 rpm to ensure that the metal hydride particles can be evenly dispersed in the liquid organic hydrogen carrier to form a stable slurry mixture.
[0016] During the stirring process, a quantitative interface modifier is added to improve the interface adhesion between the metal hydride and the liquid organic hydrogen carrier, enhance the stability of the composite system, and prevent particle sedimentation. The stirring temperature is controlled at 20-60°C, and the amount of interface modifier added is between 0.1% and 2% of the mass of the metal hydride.
[0017] S4, post-processing of the material, subjecting the uniformly mixed composite slurry obtained in the above steps to natural and slow cooling to volatilize the solvent in the mixture and ensure that the composite slurry remains stable at room temperature. During this process, some interfacial modifiers or polymers may form a thin film, further enhancing the stability of the composite material;
[0018] The prepared slurry hydrogen storage material is stored in a sealed container and avoided from exposure to air to prevent it from reacting with oxygen or moisture. The temperature is controlled between 1-5℃ / min to avoid bubbles or unevenness caused by internal stress of the material due to too rapid cooling or rapid volatilization of the solvent. The cooling process is 1-6h to ensure that the solvent is fully volatilized and the material is cooled to room temperature (20-25℃). In order to prevent oxygen or moisture in the air from entering, the container should be filled with inert gas (such as nitrogen, argon). Especially when stored in an environment with high temperature or high humidity, the temperature of the storage environment should be maintained in the range of 20-25℃, and the humidity of the storage environment should be controlled at 40-60%RH.
[0019] S5. Material performance testing: The prepared slurry hydrogen storage material is subjected to hydrogenation and dehydrogenation cycle tests. By using an atmosphere control system (such as a hydrogen flow meter, temperature control system, etc.), the hydrogenation and dehydrogenation rates are tested under different temperature and pressure conditions. The hydrogenation reaction temperature should be controlled between 100-300°C, and the dehydrogenation temperature should be higher than the hydrogenation temperature to ensure good hydrogen release performance. Multiple cycle tests are performed to evaluate the stability of the material during multiple hydrogen absorption and desorption processes, focusing on the maintenance of hydrogen storage capacity and changes in reaction rate.
[0020] The hydrogen flow rate should be stably controlled at 10-50 mL / min. The hydrogen pressure during the hydrogenation process should generally be controlled between 3-10 MPa. The dehydrogenation reaction time depends on the dehydrogenation temperature and the hydrogen storage capacity of the material. It takes 2-6 hours to complete the dehydrogenation process. In order to evaluate the stability and hydrogen storage performance of the material, at least 50-100 hydrogenation-dehydrogenation cycle tests are carried out.
[0021] A slurry hydrogen storage material is prepared by the above preparation method.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention improves the overall hydrogen storage capacity by selecting a metal hydride with a high hydrogen storage capacity (such as magnesium hydride MgH2) and compounding it with a liquid organic hydrogen carrier, partially compensating for the low hydrogen storage capacity of the liquid hydrogen carrier itself. A high shear mixer is used to evenly disperse the metal hydride in the liquid hydrogen carrier, and an interface modifier (such as PVA, PU) is added to improve the interface contact between the two, enhance the stability of the composite material, and prevent particle sedimentation, thereby improving the hydrogen storage efficiency.
[0024] 2. The slow cooling and strict storage conditions (using inert gas protection) of the present invention effectively reduce the impact of volume changes and maintain the uniformity and stability of the material. By using an atmosphere control system to accurately control the temperature and pressure during the hydrogenation and dehydrogenation processes and conducting multiple cycle tests, it is ensured that the material can still maintain stable hydrogen absorption and release performance when the operating conditions fluctuate;
[0025] In summary, the slurry hydrogen storage material prepared by the preparation method of the present application, compared with traditional slurry hydrogen storage materials, the composite of metal hydride and liquid hydrogen carrier makes up for the insufficient hydrogen storage capacity of the liquid hydrogen carrier and improves the overall hydrogen storage capacity. Through interface modification, uniform stirring and optimized cooling and storage conditions, the performance degradation of the hydrogen storage material caused by temperature and humidity changes is avoided. Multiple cycle tests ensure the stability of the material in long-term use and high hydrogen storage efficiency. DETAILED DESCRIPTION
[0026] The following will clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0027] Example 1
[0028] A method for preparing a slurry hydrogen storage material, wherein the slurry hydrogen storage material is prepared by mixing a metal hydride, a liquid organic hydrogen carrier, and an additive, and specifically comprises the following steps:
[0029] S1. Prepare raw materials and select magnesium hydride (MgH2) as the metal hydride. The preparation of metal hydride is to place commercial magnesium powder or magnesium alloy in a high-pressure hydrogen environment at a temperature of 180°C for hydrogenation reaction to obtain magnesium hydride (MgH2). This process is obtained by atmosphere hydrogenation method or directly using hydrogen to react with metallic magnesium;
[0030] Furthermore, methylcycloolefin (MCH) was selected as the liquid organic hydrogen carrier;
[0031] Furthermore, polyvinyl alcohol (PVA) was selected as an additive to improve the interfacial adhesion between metal hydrides and liquid hydrogen carriers;
[0032] Furthermore, the molar ratio of the metal hydride to the liquid organic hydrogen carrier is 3.36:1, and the additive does not participate in the storage of hydrogen and is not included in the molar ratio of hydrogen.
[0033] S2. Pre-treating the raw materials: preparing the metal hydride into powder to ensure that its particle size is 1-5 μm. Drying the obtained metal hydride powder in a vacuum environment to remove excess moisture and hydrogen, keeping it dry to avoid reaction with moisture in the air;
[0034] Furthermore, the liquid organic hydrogen carrier is purified by distillation to ensure its chemical purity. Activated carbon is used as an adsorbent to remove moisture and other harmful substances from the organic hydrogen carrier. The liquid organic hydrogen carrier is placed in a vacuum distillation apparatus and the pressure is reduced to evaporate the substance at a lower temperature. The purity of the liquid organic hydrogen carrier is required to reach ≥99%.
[0035] Furthermore, the liquid organic hydrogen carrier is mixed with activated carbon, stirred for 10 minutes, and the mixture is filtered. The activated carbon adsorbs impurities on its surface. The filtered liquid will be a pure organic hydrogen carrier. The liquid organic hydrogen carrier requires that the particulate impurities do not exceed 0.01wt% (10ppm) and the volatile organic impurities (such as low-boiling point organic compounds) are <1000ppm (ideally <500ppm).
[0036] S3. Mixing of materials: In a closed stirring container, add the metal hydride powder to the liquid organic hydrogen carrier and use a high shear mixer to mix them evenly. The stirring speed is set at 800 rpm to ensure that the metal hydride particles can be evenly dispersed in the liquid organic hydrogen carrier to form a stable slurry mixture.
[0037] Furthermore, during the stirring process, a quantitative interface modifier is added to improve the interfacial adhesion between the metal hydride and the liquid organic hydrogen carrier, enhance the stability of the composite system, and prevent particle sedimentation. The stirring temperature is controlled at 25°C, and the amount of interface modifier added is 0.1% of the weight of the metal hydride.
[0038] S4, post-processing of the material, subjecting the uniformly mixed composite slurry obtained in the above steps to natural and slow cooling to volatilize the solvent in the mixture and ensure that the composite slurry remains stable at room temperature. During this process, some interfacial modifiers or polymers may form a thin film, further enhancing the stability of the composite material;
[0039] Furthermore, the prepared slurry hydrogen storage material is stored in a sealed container to avoid exposure to air to prevent it from reacting with oxygen or moisture. The temperature is controlled at 1°C / min to avoid bubbles or unevenness caused by internal stress of the material due to excessive cooling or rapid volatilization of the solvent. The cooling process is 2h to ensure that the solvent is fully volatilized and the material is cooled to room temperature of 20°C. In order to avoid the entry of oxygen or moisture in the air, the container should be filled with inert gas argon. Especially when stored in an environment with high temperature or high humidity, the temperature of the storage environment should be maintained at 25°C and the humidity of the storage environment should be controlled at 40% RH.
[0040] S5. Material performance testing: The prepared slurry hydrogen storage material is subjected to hydrogenation and dehydrogenation cycle tests. By using an atmosphere control system (such as a hydrogen flow meter and temperature control system), the hydrogenation and dehydrogenation rates are tested under different temperature and pressure conditions. The hydrogenation reaction temperature should be controlled at 100°C, and the dehydrogenation temperature should be higher than the hydrogenation temperature to ensure good hydrogen release performance. The stability of the material during multiple hydrogen absorption and desorption processes is evaluated through multiple cycle tests, focusing on the maintenance of hydrogen storage capacity and changes in reaction rate.
[0041] Furthermore, the hydrogen flow rate should be stably controlled at 10 mL / min, the hydrogen pressure during the hydrogenation process should generally be controlled at 3 MPa, the dehydrogenation reaction time depends on the dehydrogenation temperature and the hydrogen storage capacity of the material, and the dehydrogenation process is completed in 4 h. In order to evaluate the stability and hydrogen storage performance of the material, at least 50 hydrogenation-dehydrogenation cycle tests are carried out.
[0042] Example 2
[0043] A method for preparing a slurry hydrogen storage material, wherein the slurry hydrogen storage material is prepared by mixing a metal hydride, a liquid organic hydrogen carrier, and an additive, and specifically comprises the following steps:
[0044] S1. Prepare raw materials and select sodium aluminum hydride (NaAlH4) as the metal hydride. The preparation of metal hydride is to place commercial magnesium powder or magnesium alloy in a high-pressure hydrogen environment at a temperature of 200°C for hydrogenation reaction to obtain sodium aluminum hydride (NaAlH4). This process directly uses hydrogen to react with metallic magnesium;
[0045] Furthermore, tetralin is selected as the liquid organic hydrogen carrier;
[0046] Furthermore, polyurethane (PU) was selected as an additive to improve the interfacial adhesion between metal hydride and liquid hydrogen carrier;
[0047] Furthermore, the molar ratio of the metal hydride to the liquid organic hydrogen carrier is 3.36:1, and the additive does not participate in the storage of hydrogen and is not included in the molar ratio of hydrogen.
[0048] S2. Pre-treating the raw materials: preparing the metal hydride into powder to ensure that its particle size is 2 μm. Drying the obtained metal hydride powder in a vacuum environment to remove excess moisture and hydrogen, keeping it dry to avoid reaction with moisture in the air;
[0049] Furthermore, the liquid organic hydrogen carrier is purified by filtration or distillation to ensure its chemical purity. An adsorbent such as activated carbon is used to remove moisture and other harmful substances from the organic hydrogen carrier. The liquid organic hydrogen carrier is placed in a vacuum distillation device to reduce the pressure and evaporate the substance at a lower temperature. The purity of the liquid organic hydrogen carrier is required to reach ≥99%.
[0050] Furthermore, the liquid organic hydrogen carrier is mixed with activated carbon, stirred for 12 minutes, and the mixture is filtered. The activated carbon adsorbs impurities on its surface. The filtered liquid will be a pure organic hydrogen carrier. The liquid organic hydrogen carrier requires that the particulate impurities do not exceed 0.01wt% (10ppm) and the volatile organic impurities (such as low-boiling point organic compounds) are <1000ppm (ideally <500ppm).
[0051] S3. Mixing of materials: In a closed stirring container, add the metal hydride powder to the liquid organic hydrogen carrier and use a high shear mixer to mix them evenly. The stirring speed is set at 1000 rpm to ensure that the metal hydride particles can be evenly dispersed in the liquid organic hydrogen carrier to form a stable slurry mixture.
[0052] Furthermore, during the stirring process, a quantitative interface modifier is added to improve the interfacial adhesion between the metal hydride and the liquid organic hydrogen carrier, enhance the stability of the composite system, and prevent particle sedimentation. The stirring temperature is controlled at 30°C, and the amount of interface modifier added is 2% of the mass of the metal hydride.
[0053] S4, post-processing of the material, subjecting the uniformly mixed composite slurry obtained in the above steps to natural and slow cooling to volatilize the solvent in the mixture and ensure that the composite slurry remains stable at room temperature. During this process, some interfacial modifiers or polymers may form a thin film, further enhancing the stability of the composite material;
[0054] Furthermore, the prepared slurry hydrogen storage material is stored in a sealed container to avoid exposure to air to prevent it from reacting with oxygen or moisture. The temperature is controlled at 4°C / min to avoid bubbles or unevenness caused by internal stress of the material due to excessive cooling or rapid volatilization of the solvent. The cooling process is 3h to ensure that the solvent is fully volatilized and the material is cooled to room temperature of 22°C. In order to avoid the entry of oxygen or moisture in the air, the container should be filled with inert gas argon. Especially when stored in an environment with high temperature or high humidity, the temperature of the storage environment should be maintained within 25°C and the humidity of the storage environment should be controlled at 50% RH.
[0055] S5. Material performance testing: The prepared slurry hydrogen storage material is subjected to hydrogenation and dehydrogenation cycle tests. By using an atmosphere control system (such as a hydrogen flow meter and temperature control system), the hydrogenation and dehydrogenation rates are tested under different temperature and pressure conditions. The hydrogenation reaction temperature should be controlled at 1250°C, and the dehydrogenation temperature should be higher than the hydrogenation temperature to ensure good hydrogen release performance. The stability of the material during multiple hydrogen absorption and desorption processes is evaluated through multiple cycle tests, focusing on the maintenance of hydrogen storage capacity and changes in reaction rate.
[0056] Furthermore, the hydrogen flow rate should be stably controlled at 30 mL / min, and the hydrogen pressure during the hydrogenation process should generally be controlled at 5 MPa. The time of the dehydrogenation reaction depends on the dehydrogenation temperature and the hydrogen storage capacity of the material. It takes 46 hours to complete the dehydrogenation process. In order to evaluate the stability and hydrogen storage performance of the material, at least 70 hydrogenation-dehydrogenation cycle tests are carried out.
[0057] Example 3
[0058] A method for preparing a slurry hydrogen storage material, wherein the slurry hydrogen storage material is prepared by mixing a metal hydride, a liquid organic hydrogen carrier, and an additive, and specifically comprises the following steps:
[0059] S1. Prepare raw materials and select calcium hydride (CaH2) as the metal hydride. The preparation of metal hydride is to place commercial magnesium powder or magnesium alloy in a high-pressure hydrogen environment at a temperature of 220°C for hydrogenation reaction to obtain calcium hydride (CaH2). This process is obtained by atmosphere hydrogenation method;
[0060] Furthermore, tetralin was selected as the liquid organic hydrogen carrier;
[0061] Furthermore, polyurethane (PU) was selected as an additive to improve the interfacial adhesion between metal hydride and liquid hydrogen carrier;
[0062] Furthermore, the molar ratio of the metal hydride to the liquid organic hydrogen carrier is 3.36:1, and the additive does not participate in the storage of hydrogen and is not included in the molar ratio of hydrogen.
[0063] S2. Pre-treating the raw materials: preparing the metal hydride into powder to ensure that its particle size is 5 μm. Drying the obtained metal hydride powder in a vacuum environment to remove excess water and hydrogen, keeping it dry to avoid reaction with moisture in the air;
[0064] Furthermore, the liquid organic hydrogen carrier is purified by filtration or distillation to ensure its chemical purity. Activated carbon is used as an adsorbent to remove moisture and other harmful substances from the organic hydrogen carrier. The liquid organic hydrogen carrier is placed in a vacuum distillation apparatus and the pressure is reduced to evaporate the substance at a lower temperature. The purity of the liquid organic hydrogen carrier is required to reach ≥99%.
[0065] Furthermore, the liquid organic hydrogen carrier is mixed with activated carbon, stirred for 10-20 minutes, and the mixture is filtered. The activated carbon adsorbs impurities on its surface. The filtered liquid will be a pure organic hydrogen carrier. The liquid organic hydrogen carrier requires that the particulate impurities do not exceed 0.01wt% (10ppm) and the volatile organic impurities (such as low-boiling point organic compounds) are <1000ppm (ideally <500ppm).
[0066] S3. Mixing of materials: In a closed stirring container, add the metal hydride powder to the liquid organic hydrogen carrier and use a high shear mixer to mix them evenly. The stirring speed is set at 1800 rpm to ensure that the metal hydride particles can be evenly dispersed in the liquid organic hydrogen carrier to form a stable slurry mixture.
[0067] Furthermore, during the stirring process, a quantitative interface modifier is added to improve the interfacial adhesion between the metal hydride and the liquid organic hydrogen carrier, enhance the stability of the composite system, and prevent particle sedimentation. The stirring temperature is controlled at 50°C, and the amount of interface modifier added is 2% of the weight of the metal hydride.
[0068] S4, post-processing of the material, subjecting the uniformly mixed composite slurry obtained in the above steps to natural and slow cooling to volatilize the solvent in the mixture and ensure that the composite slurry remains stable at room temperature. During this process, some interfacial modifiers or polymers may form a thin film, further enhancing the stability of the composite material;
[0069] Furthermore, the prepared slurry hydrogen storage material is stored in a sealed container to avoid exposure to air to prevent it from reacting with oxygen or moisture. The temperature is controlled at 5°C / min to avoid bubbles or unevenness caused by internal stress of the material due to excessive cooling or rapid volatilization of the solvent. The cooling process is 5h to ensure that the solvent is fully volatilized and the material is cooled to room temperature of 25°C. In order to avoid the entry of oxygen or moisture in the air, the container should be filled with an inert gas such as nitrogen. Especially when stored in an environment with high temperature or high humidity, the temperature of the storage environment should be maintained within 25°C and the humidity of the storage environment should be controlled at 60% RH.
[0070] S5. Material performance testing: The prepared slurry hydrogen storage material is subjected to hydrogenation and dehydrogenation cycle tests. By using an atmosphere control system and temperature control system, the hydrogenation and dehydrogenation rates are tested under different temperature and pressure conditions. The hydrogenation reaction temperature should be controlled at 250°C, and the dehydrogenation temperature should be higher than the hydrogenation temperature to ensure good hydrogen release performance. The stability of the material during multiple hydrogen absorption and desorption processes is evaluated through multiple cycle tests, focusing on the maintenance of hydrogen storage capacity and changes in reaction rate.
[0071] Furthermore, the hydrogen flow rate should be stably controlled at 45 mL / min, and the hydrogen pressure during the hydrogenation process should generally be controlled at 9 MPa. The dehydrogenation reaction time depends on the dehydrogenation temperature and the hydrogen storage capacity of the material. It takes 6 hours to complete the dehydrogenation process. In order to evaluate the stability and hydrogen storage performance of the material, at least 80 hydrogenation-dehydrogenation cycle tests are carried out.
[0072] Table 1: Performance of the three embodiments described above in terms of material performance testing
[0073]
[0074] A conventional slurry hydrogen storage material (ammonia borane) in the field was selected as a control example and compared with the above three examples in terms of hydrogen storage capacity, cycle stability, desorption performance, and specific surface area. Hydrogen storage capacity is a key indicator for measuring the hydrogen storage capacity of a material, indicating the ratio of the mass of hydrogen that the material can store to its own mass. Excellent slurry hydrogen storage materials should have a high hydrogen storage capacity. Generally, a hydrogen storage capacity greater than 5wt% is considered good, and above 10wt% is considered excellent.
[0075] After multiple hydrogenation-dehydrogenation cycles, the hydrogen storage material should be able to maintain good hydrogen storage capacity and reaction rate. The test is usually carried out for dozens to hundreds of cycles. The hydrogen absorption and release performance of the material should be stable without significant degradation. The hydrogenation capacity retention rate of the material is a key indicator of its stability. The capacity retention rate of excellent materials should be above 90%;
[0076] Evaluate the desorption pressure and temperature of hydrogen. Generally, high-quality hydrogen storage materials can quickly dehydrogenate at lower temperatures (such as 200-350°C) without the need for excessive temperatures or pressures.
[0077] The specific surface area of the material has a significant impact on the adsorption capacity of hydrogen. A larger specific surface area usually provides more adsorption sites, thereby increasing the hydrogen storage capacity. The ideal slurry hydrogen storage material should have a larger specific surface area. Generally, the larger the specific surface area, the better the hydrogen storage performance. Summary: The slurry hydrogen storage material obtained under the preparation method of the experimental group is significantly higher than the traditional conventional slurry hydrogen storage material in terms of hydrogen storage capacity, cycle stability, desorption performance and specific surface area, indicating that this new slurry hydrogen storage material has good hydrogen storage performance and stability.
[0078] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.
Claims
1. A method for preparing a slurry hydrogen storage material, characterized in that: The slurry hydrogen storage material is prepared by mixing metal hydride, liquid organic hydrogen carrier and additive, and specifically includes the following steps: S1. Prepare raw materials, and select one of magnesium hydride (MgH2), sodium aluminum hydride (NaAlH4), and calcium hydride (CaH2) as the metal hydride. Select one of methylcycloolefin (MCH) and tetralin as the liquid organic hydrogen carrier. Polyvinyl alcohol (PVA) or polyurethane (PU) is selected as an additive to improve the interfacial adhesion between the metal hydride and the liquid hydrogen carrier; S2. Pre-treat the raw materials, make the metal hydride into powder, ensure that its particle size is 1-5μm, dry the obtained metal hydride powder in a vacuum environment to remove excess water and hydrogen. Purify the liquid organic hydrogen carrier by filtration or distillation to ensure its chemical purity, and use adsorbent activated carbon to remove moisture and other harmful substances in the organic hydrogen carrier; S3. Mixing of materials: In a closed stirring container, add the metal hydride powder to the liquid organic hydrogen carrier and mix them evenly using a high shear mixer at a stirring speed of 500-2000 rpm. During the stirring process, a quantitative interfacial modifier is added; S4, post-processing of the material, the uniformly mixed composite slurry material obtained in the above steps is naturally and slowly cooled to evaporate the solvent in the mixture. The prepared slurry hydrogen storage material is stored in a sealed container and is not exposed to air to prevent it from reacting with oxygen or moisture; S5. Material performance test: The prepared slurry hydrogen storage material is subjected to hydrogenation and dehydrogenation cycle tests. By using the hydrogen flow meter of the atmosphere control system, the hydrogenation and dehydrogenation rates are tested under different temperature and pressure conditions. The hydrogenation reaction temperature should be controlled between 100-300°C, and the dehydrogenation temperature should be higher than the hydrogenation temperature.
2. The method for preparing a slurry hydrogen storage material according to claim 1, characterized in that: The preparation of the metal hydride in step S1 is to place commercial magnesium powder or magnesium alloy in a high-pressure hydrogen environment and perform a hydrogenation reaction at a temperature between 180-220° C. to obtain magnesium hydride (MgH2), and this process is obtained by an atmosphere hydrogenation method.
3. The method for preparing a slurry hydrogen storage material according to claim 1, characterized in that: In step S1, the molar ratio of the metal hydride to the liquid organic hydrogen carrier is 3.36:1, and the additive does not participate in the storage of hydrogen and is not included in the molar ratio of hydrogen.
4. The method for preparing a slurry hydrogen storage material according to claim 1, characterized in that: In the step S2, a vacuum distillation method is adopted, and the liquid organic hydrogen carrier is placed in a vacuum distillation device, and the substance is evaporated at a relatively low temperature by reducing the pressure. The purity of the liquid organic hydrogen carrier is required to reach ≥99%.
5. The method for preparing a slurry hydrogen storage material according to claim 1, characterized in that: In step S2, activated carbon filtration is adopted to mix the liquid organic hydrogen carrier with activated carbon, stir for 10-20 minutes, filter the mixed liquid, and the activated carbon adsorbs impurities on its surface. The filtered liquid will be a pure organic hydrogen carrier. The liquid organic hydrogen carrier requires that the particulate impurities do not exceed 0.01wt% (10ppm), and the volatile organic impurities (such as low boiling point organic compounds) are <1000ppm (ideally <500ppm).
6. The method for preparing a slurry hydrogen storage material according to claim 1, characterized in that: In step S3, the stirring temperature is controlled at 20-60° C., and the amount of the interface modifier added is between 0.1% and 2% of the mass of the metal hydride.
7. The method for preparing a slurry hydrogen storage material according to claim 1, characterized in that: In step S4, the temperature is controlled between 1-5°C / min to ensure that the solvent is fully volatilized and the material is cooled to room temperature (20-25°C). In order to prevent oxygen or moisture in the air from entering, the container should be filled with inert gas (such as nitrogen, argon), the temperature of the storage environment should be maintained in the range of 20-25°C, and the humidity of the storage environment should be controlled at 40-60%RH.
8. The method for preparing a slurry hydrogen storage material according to claim 1, characterized in that: In step S5, the hydrogen flow rate should be stably controlled at 10-50 mL / min, the hydrogen pressure during the hydrogenation process should generally be controlled between 3-10 MPa, the dehydrogenation reaction time depends on the dehydrogenation temperature and the hydrogen storage capacity of the material, and it takes 2-6 hours to complete the dehydrogenation process. In order to evaluate the stability and hydrogen storage performance of the material, at least 50-100 hydrogenation-dehydrogenation cycle tests are performed.
9. A slurry hydrogen storage material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.